Seawater evaporation using natural flow solar still - Andika Cahya Putra Pratama; Dan Mugisidi; Oktarina Heriyani (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
One-third of the world's population, including coastal communities in Indonesia, experiences a shortage of clean water for daily needs. By 2050, it is estimated that around 25% of the world's population will be affected by the clean water crisis. This research is directed at examining the role of natural airflow in a solar still system in determining the evaporation rate during the seawater desalination process. Water temperature has a significant influence on solar still performance, where increasing water temperature and airflow velocity within the system will increase the evaporation rate. This research focuses on measuring the evaporation rate of seawater in a solar still device that relies on natural flow as its working mechanism. The desalination process is equipped with a condenser that functions to convert water vapor into liquid. In addition, there is a measurement system that includes temperature parameters and airflow velocity to ensure effective operation and precise data monitoring. Evaporation data was collected periodically every 15 minutes during a two-day observation period, to conduct a comprehensive analysis of the desalination system's performance. Research results show that the use of solar energy with natural flow can effectively accelerate the evaporation rate. The average experimental result is 231 grams and the theoretical result is 174 grams, with a percentage of 57%. This system has the potential to increase the efficiency of the desalination process, especially if developed according to local climate conditions that affect the overall performance of the device